PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI MANAJEMEN, METODE PENGUKURAN KINERJA DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL PADA RUMAH SAKIT ESTOMIHI MEDAN - Melanthon Rumapea; Jaminta Sinaga; Ririn Elvani Saragih (Universitas Methodist Indonesia, 2018)
This research was conducted to examine the influence of the application of management accounting information system,performance measurement method,and reward system on the performance of managerial at field estomihi hospital. Population of 47 people.sampling technique is using saturated samples.the data used in secondary data from estomihi hospital.the test used in this using multiple liner regression. Result of research based on hyphotesis test show that partially management accounting information system and performance measurement methods have positive and significant effect on manajerial performance. Eventhought reward system have a positive and insignificant effect on manajerial performance. And simultaneously the accounting information system of management performance measurement method of reward system has a positive and significant impact on managerial performance. Based on the coefficient of determination Adjusted (R2), having results of 0,322. It means independent variable influences application of management accounting information system,performance measurement method,and reward system of the dependent variables performance of managerial can be described by this equation of 32,2%. While the rest of 67,8% is explained by other factors that are not included in the regression model.